2023
DOI: 10.1002/cjoc.202200845
|View full text |Cite
|
Sign up to set email alerts
|

DNA Reaction Network Mimicking the Basic Steps of Synaptic Communication

Abstract: Comprehensive Summary Biological systems use intricate networks of chemical reactions to exchange information. How to simulate complex systems with simple strand‐displacement reactions is crucial to broaden the application scenario of the DNA reaction network. Here, we report the artificial DNA reaction network to mimic the operation and function of biological information transfer via strand‐displacement reaction. DNA is used as simple artificial analogs to schematize structures and transmit information. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Meanwhile, the activity of intracellular nuclear factor κB (NF-κB) signaling pathway and the phosphorylation level of mitogen-activated protein kinase (MAPK) are decreased to delay the process of development of Alzheimer's disease. 19 Some scholars have reported that loganin mainly reduces the level of MPTP-induced autophagosomes by increasing the digestive effect of lysosomes on autophagosomes in PC12 cells, thus playing a role in anti-Parkinson's disease (PD). 20 In addition, loganin has a good pharmacological effect in the prevention and treatment of diabetes, 21 synovial inflammation in rats, 22 intervention in the oxidative damage of ARPE-19 human retinal pigment epithelial cells, 23 and relief of gout inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the activity of intracellular nuclear factor κB (NF-κB) signaling pathway and the phosphorylation level of mitogen-activated protein kinase (MAPK) are decreased to delay the process of development of Alzheimer's disease. 19 Some scholars have reported that loganin mainly reduces the level of MPTP-induced autophagosomes by increasing the digestive effect of lysosomes on autophagosomes in PC12 cells, thus playing a role in anti-Parkinson's disease (PD). 20 In addition, loganin has a good pharmacological effect in the prevention and treatment of diabetes, 21 synovial inflammation in rats, 22 intervention in the oxidative damage of ARPE-19 human retinal pigment epithelial cells, 23 and relief of gout inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…DNA, owing to its biocompatibility and cost-effectiveness in synthesis, as well as the programmability and predictability afforded by Watson–Crick base-pairing, stands out as an engineering material . DNA nanotechnology, which focuses on the construction of artificial DNA structures, plays a crucial role in various applications, such as biosensing, disease diagnosis, , cancer therapy, ,, artificial networks, and the development of artificial molecular machines. …”
mentioning
confidence: 99%